Understanding Youth Attraction to Designer Clothing - Nagdevani, Dev; Petel, Bhavya; Jaju, Pooja; Sah, Aditya; Sapra, Ruchi; Kacchara, Gul; Chauhan, Rahul; Maseleno, Andino (Greenation International Journal of Tourism and Management, 2024)
This research paper investigates the impact of designer clothing on youngsters, focusing on their perceptions, motivations, and the associated social dynamics. Through an analysis of variance (ANOVA), the study explores key questions surrounding the appeal of designer brands, common criticisms, and potential negative consequences of such consumption. The results indicate that while many youths are attracted to designer apparel for its status and quality, they also express concerns regarding its exclusivity and the pressure to conform to social expectations. Notably, the analysis reveals significant differences in perceptions about the negative consequences of wearing designer clothes, highlighting a recognition among youngsters of the potential for social isolation or financial strain associated with high-fashion choices. Additionally, the study examines how designer brands market their products to appeal to a younger audience, identifying strategies that leverage social media and influencer marketing. Overall, the findings illustrate a complex interplay between fashion choices, identity formation, and peer relationships in the lives of young consumers. This paper contributes to a broader understanding of how designer clothing influences youth culture and consumer behavior in contemporary society, providing valuable insights for marketers, educators, and parents.